Gender, culture, and consumer behavior - Otnes, Cele, 1960-; Tuncay-Zayer, Linda (Routledge, 2012)
"When considering how we should introduce this volume, we reflected on our own lives as women who both grew up in America, but whose heritages are distinct. We are both daughters of male liberal arts professors who provided most of the family income, while our mothers focused on child-rearing and community activities, as well as by-choice educational pursuits and forays into the working world. Linda is a first-generation American whose parents emigrated to the U.S. in 1970. Cele's ancestors were early U.S. settlers whose families relied on hard work and the G.I. Bill to fend off blows dealt by the Depression. We decided to offer examples of how gender, culture and consumption intersect in memories that demonstrate the dramatic and dynamic changes in these three areas over our lifetimes"--Vydavatelská anotace
Terminologický slovník
Keywords: spotřebitelské chování; sociologie spotřeby; gender; consumer behavior; sociology of consumption; kolektivní monografie; collective monographs